Oriented Attachment: A Unique Mechanism for the Colloidal Synthesis of Metal Nanostructures. Issue 3 (13th January 2022) - Chen, Ruhui; Nguyen, Quynh N.; Xia, Younan
Abstract: Rational synthesis of nanostructures with desired properties critically depends on our understanding of the growth mechanism. In addition to the traditional mechanism involving atomic addition, oriented attachment (OA) has received increasing attention in recent years. Employing nanocrystallites as building blocks, OA offers an important route to anisotropic growth, inclusion of defects, and formation of nanostructures with branched morphology. With a focus on metals, here we offer a brief account of recent progress in understanding OA and how it can be adapted for the colloidal synthesis of nanostructures with diverse compositions and morphologies. We start with a discussion on the current understanding of OA based on computational simulations and experimental studies, followed by typical examples of metal nanostructures produced through OA. Finally, we showcase the catalytic and plasmonic applications enabled by those nanostructures, together with perspectives on the challenges and opportunities. Abstract : As a unique route to the colloidal synthesis of nanostructures, oriented attachment involves the coalescence of nanocrystallites, followed by the alignment of their crystal lattices to form one single particle with different shapes and morphologies.